IMPLEMENTASI SISTEM PAKAR UNTUK PENDETEKSI KERUSAKAN MOTOR DENGAN MENGGUNAKAN METODE FORWARD CHAINNING BERBASIS WEB - Muhammad Aji Wisnu Perdana; Thoyyibah T (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Motorized vehicles are a means of transportation that are widely used so that it is not uncommon for many enthusiasts such as the convenience obtained in shortening travel time. In addition, the uniqueness of the form of motorized vehicles that have a small shape that makes it easier when driving on narrow and jammed roads. However, in addition to the convenience obtained from motorized vehicles, damage often occurs due to continuous use without paying attention to the vehicle, therefore vehicle owners are required to service the motorized vehicle. Repair errors still often occur because the submission of complaints is different from the damage on the motor, causing the motor vehicle to be damaged again a few days later and result in losses to the customer. The occurrence of this error makes the technician have to check twice to ensure the damage to the motor which takes quite a long time. customers also feel confused in determining which damage many of the customers are unfamiliar with motorcycle engines. This makes the customer feel worried that the damage to the motorbike will be exaggerated. The methods used in obtaining data are observation, insight and literature study and in system development using an expert system with the forward chaining method, the expert syste is composed of two main parts, namely the development environment and consulting environment and also helps mechanics in solving the problem of motorcycle engine damage. From the results of the study, it is hoped that the expert system can help solve problems in detecting motor damage.